Analisis Peramalan Jumlah Penumpang Kereta Api dan Kapasitas Lintas Jalur Kertosono-Blitar dan Blitar-Kertosono - Amrita Winaya; Dani Novan; Muhammad Hidayat (Universitas Nusa Putra, 2023)
On the southern Java railroad there is a detour line, this line passes through Kertosono Station, Wonokromo Station, Bangil Station, Malang Station, Blitar Station, and returns to Kertosono Station. This research is focused on the train line from Kertosono Station to Blitar Station with a distance of 81.17 km. Local train trips on this line still use single tracks so they have to wait to cross with long-distance trains. This study was conducted to determine the potential of the Kertosono-Blitar train line in the future. The methods used to predict the number of train passengers are linear regression and exponential smoothing methods, and to determine the existing cross capacity, the Supriyadi method is used. From the results of the forecasting analysis, the number of passengers is estimated from 2019 to 2030 to increase to 15079 people from Kertosono Station to Blitar Station, while from Blitar Station to Kertosono Station, an increase of 11033 passengers was obtained in 2030. When viewed from the calculation of the existing cross capacity, the Kertosono-Blitar railway line is still feasible to operate, because the maximum daily cross limit is 43 trains per day so this line still does not require an upgrade to double track.